Multimedia como herramienta de comunicación y su influencia en el aprendizaje del público infantil enfocado en la violencia en contra de la mujer, en niños de 9 a 11 años, en la Escuela María Leonor Salgado en la ciudad de Quito. - Proaño Guevara, Mayerli Anahi (2023)
The present research project aims to analyze multimedia as a field for teaching about violence against women, focusing on children aged 9 to 11 at María Leonor Salgado School in the city of Quito. The project includes investigating the background of the issue, identifying specific pedagogical needs of children in this age group, producing a multimedia element that clearly conveys the necessary values to prevent violence against women, and creating a multimedia element based on the research findings. The methodology used to develop the multimedia is based on User-Centered Design (UCD), which involves qualitative research through interviews, defining specific requirements, designing content, and its implementation. The main results indicated that the majority of children showed sustained attention and appropriate interest in the presented content. The project's impact was evident in various aspects. In the technological aspect, the implementation of a multimedia tool promoted the development of digital skills in children and provided teachers with a modern tool to enhance their educational work. In the social aspect, the project raised awareness among children about violence against women and fostered attitudes of respect, equality, and prevention from an early age. Additionally, the environmental impact was reduced thanks to the digital format of the multimedia, avoiding waste generation.